APLIKASI QUIZIZZ DALAM PEMBELAJARAN DARING MATEMATIKA PADA SISWA SDN SIMOKERTO VI/139 SURABAYA - Lilik Setiari (Universitas Tribhuwana Tunggadewi, 2021)
This study aims to determine an increase in student learning outcomes, as well as to describe teacher activities using the Quizizz application in learning mathematics in class II SDN Simokerto VI/139 Surabaya. The research conducted is Classroom Action Research with data collection techniques using tests, observations, and questionnaires. The results showed that the Quizizz application could improve student learning outcomes in cycle I by 67, cycle II by 78, and cycle III by 87. In addition, it can increase teacher activity, student activity, scientific and psychomotor attitudes of students in learning mathematics in spatial building materials.